2004
DOI: 10.5713/ajas.2004.1123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Xylose on the Growth of Broilers and Nutrient Digestibility as well as Absorption of Xylose in the Portal-drained Viscera

Abstract: Two experiments were conducted to examine the effects of dietary inclusion of xylose on growth performance, nutrient digestibility and xylose absorption in the portal-drained viscera of broiler chicks. In Exp. 1, ninety male 14 day-old broilers were used to study the effects of different inclusion levels (0, 5, 10, 20 and 40%) of D-xylose in the semi-purified diets on the growth and nutrient digestibility of broilers. In Exp. 2, One hundred and eight male broilers, fed by precision feeding at 22 day-old, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…In the fasted state, hepatic pyruvate carboxylase was linearly increased by xylose [ 19 ]. Because pyruvate carboxylase is a rate limiting enzyme for hepatic gluconeogenesis which is active when glycogen stores are depleted, such as occurs in starvation, this result corroborates reports that xylose depletes hepatic glycogen stores in poultry [ 18 , 39 ].…”
Section: Xylose Metabolismsupporting
confidence: 85%
“…In the fasted state, hepatic pyruvate carboxylase was linearly increased by xylose [ 19 ]. Because pyruvate carboxylase is a rate limiting enzyme for hepatic gluconeogenesis which is active when glycogen stores are depleted, such as occurs in starvation, this result corroborates reports that xylose depletes hepatic glycogen stores in poultry [ 18 , 39 ].…”
Section: Xylose Metabolismsupporting
confidence: 85%
“…In this study, final BW, growth rate, and feed efficiency decreased when D-xylose content in the diets increased. These observations are in agreement with previous results in pigs (Wise et al, 1954) and chickens (Wagh and Waibel, 1966;Schutte, 1990;Schutte et al, 1992;Peng et al, 2004), who also reported decreased weight gain and feed efficiency due to increasing dietary D-xylose content. An explanation for the reduced weight gain and feed efficiency may be due to the lower ME content of D-xylose compared with GLU as reported by Schutte et al (1991) and Verstegen et al (1997).…”
Section: Effect Of D-xylose On Growth Performancesupporting
confidence: 93%
“…Feed intake was not affected by increasing dietary D-xylose content in the present study. In chickens, Peng et al (2004) reported that increasing dietary D-xylose content up to 40% linearly decreased feed consumption. Recently, we reported that up to 15% dietary D-xylose inclusion linearly decrease feed consumption in broiler chickens (Regassa et al, 2017).…”
Section: Effect Of D-xylose On Growth Performancementioning
confidence: 99%
See 1 more Smart Citation